Estimating heterogeneous agents behavior with different investment horizons in stock markets - Zhenxi Chen (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2014)
In addition to the traditional agent types of fundamentalists and chartists, a new dimension of investment horizon is included in evaluating historical performance of strategies. Based on the three stock markets of Japan, Hong Kong and Germany, it is found that investors with different investment horizons exist in al the markets. Regressions based on all the investment horizons produce better fitted results. Different markets can be characterized by different agents and different investment horizons. Ignorance of the heterogeneity of investment horizon may generate biased results due to the concern of omitting variables.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: G12; C22; 330; Investment horizon; Heterogeneous agents; Evolutionary selection; Behavioral finance